1965
DOI: 10.1111/j.1365-2621.1965.tb01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Palatability and Quantity of Pork as Influenced by Breed and Fatness

Abstract: SUMMARY The influence of breed, sex, and fatness on the quantity and eating quality of loins from 119 Duroc and 111 Yorkshire pigs was studied. Duroc pigs had significantly more intramuscular fat, smaller longissimus dorsi area, more tender, juicier loins, and less separable lean in the ham than Yorkshire pigs. Among Durocs, barrows had more desirable lean flavor than gilts. Among Yorkshires, barrows had more desirable fat flavor than gilts. In both breeds, an increase in backfat thickness was accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

1970
1970
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 3 publications
1
17
2
Order By: Relevance
“…The results part of the study (Kempster et al, 1986) and on eating quality do not support the butchers' the general trends associated with a reduction predictions of much lower eating quality in in fat thickness have been observed before the lean group (Kempster et al, 1986) or the (e.g. In the present study the large number P 2 and muscle lipid, a result also obtained of carcasses examined allowed a statistically by Hiner et al (1965) and Jensen et al significant difference to be detected. The lower fat suggestion that marbling fat offers a reliable quality of the uncooked fat observed in the pointer to eating quality, lean group was presumably due to the grey Effects of se (as opposed to white), 'sloppy' appearance of JJ J underdeveloped fat tissue (Wood, 1984).…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…The results part of the study (Kempster et al, 1986) and on eating quality do not support the butchers' the general trends associated with a reduction predictions of much lower eating quality in in fat thickness have been observed before the lean group (Kempster et al, 1986) or the (e.g. In the present study the large number P 2 and muscle lipid, a result also obtained of carcasses examined allowed a statistically by Hiner et al (1965) and Jensen et al significant difference to be detected. The lower fat suggestion that marbling fat offers a reliable quality of the uncooked fat observed in the pointer to eating quality, lean group was presumably due to the grey Effects of se (as opposed to white), 'sloppy' appearance of JJ J underdeveloped fat tissue (Wood, 1984).…”
Section: Resultscontrasting
confidence: 75%
“…Perceived fatness closely reflected 1965;Jensen, Craig and Robison, 1967). The overall assessment of quality in found between the concentration of lipid in the cooked chop was significantly associated muscle and backfat thickness or other indices with variation in flavour (r = 0-74), pork of carcass fatness (Duniec, Kielanowski and flavour intensity (r = 0-53) and tenderness Osiriska, 1961;Hiner et al, 1965;Jensen et (r = 0-69), but not with variation in juiciness al., 1967). One with P 2 .…”
Section: Resultsmentioning
confidence: 91%
“…Studies have been conducted regarding the affects of different breeds on growth performance, carcass composition and meat quality (Hiner et al 1964;Ellis et al 1990a;Sather et af. 1991;Lo et al 1992a).…”
Section: Genetics and Breedingmentioning
confidence: 99%
“…Generally, colored breeds (Duroc and Hampshire) exhibit superior growth and carcass characteristics while the white breeds (Large whites and Landrace) excel in the maternal traits. Studies have demonstrated the superior pork quality and palatability characteristics of the Duroc breed (Hiner et al 1964;Lo er al. 1992a).…”
Section: Genetics and Breedingmentioning
confidence: 99%
“…However, whether at high marbling fat levels (7%, as in older US studies (Hiner et al, 1965) or at lower levels (1.5%) in more recent European work, the advantage of the Duroc has been shown to be small (Table 4). Pigs of the Duroc breed contain more marbling fat than other breeds at the same overall body fatness and fat thickness and tend in some studies to produce more tender, juicy meat.…”
Section: Genetic Effects; Breed and Selectionmentioning
confidence: 96%